Pertanggung Jawaban Hukum Pengelola Parkir Terkait Legalitas Usahanya - Murahman, Farhan; Berlianty, Teng; Kuahaty, Sarah Selfina (PATTIMURA Legal Journal, 2024)
Introduction: Parking service users who are harmed because there are managers and parking attendants who manage a parking lot illegally, they do not have direct permission from the local government and there is a loss of consumer belongings, and the consumer asks for compensation for the loss but the parking officer does not want to be responsible for the reason that it is not his responsibility, this is of course the responsibility of the parking manager if the parking officer does not want to be responsible for the The loss. Purposes of the Research: The responsibility of the parking manager, this of course causes losses experienced by parking lot users or consumers due to the absence of responsibility from the parking manager. Methods of the Research: The research method used is a type of normative research that is carried out by researching library materials or secondary data, legal materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials, in the procedure for collecting legal materials is carried out by examining legal materials, preparing legal materials, systematically processing and analyzing legal materials. Results Originality of the Research: The results of this study show that the legality of parking attendants, namely parking managers, must have official permits from the local government and wear uniforms or clear identification. Sanctions given to illegal parking attendants include verbal or written reprimands and administrative fines, as well as the responsibility of parking managers to parking service users. In the event of loss of consumer goods, the parking manager is responsible for replacing the lost consumer goods, because the task of the parking manager is to protect the consignment items belonging to consumers as if they belong to them and must be returned in their original form.